(untitled) (Research, Society and Development, 2020)
Objective: Analyse reading (time to read) and writing performance of schoolchildren of third year of municipal public schools of Porto Alegre-RS metropolitan region, correlated with the socioeconomic status and parents’ schooling. Method: Seventy-six schoolchildren took part of the survey, being 41 (54%) female and 35 (46%) male, with ages between eight years and a month and nine years and nine months. Parents and/or responsable for schoolchildren received a quiz from Brazilian Research and Company Association that investigated socioeconomic and parenthood education level. To evaluate reading performance was used the Task of Reading of Words and Nonsense words Isolated. This evaluates the accuracy of the oral reading of isolated words and nonsense words. To evaluate writing the Writing after saying test (reduced version). Results: When comparing total writing errors and parental education, analysis didn’t show any difference, both for father education (p=0.7) and mather education (p=0.5), this means that total errors were independent of parental education. This tendency was already observed for total writing errors when compared to family socioeconomic level (p=0.6). Conclusion: Reading and writing performance is more related to formal writing teaching than to socioeconomic level and parental education.